2.2.124 Problems 12301 to 12400

Table 2.249: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

12301

\[ {}y^{\prime } = y^{2} f \left (x \right )-a \tan \left (\lambda x \right )^{2} \left (a f \left (x \right )-\lambda \right )+a \lambda \]

[_Riccati]

359.813

12302

\[ {}y^{\prime } = y^{2} f \left (x \right )-a \cot \left (\lambda x \right )^{2} \left (a f \left (x \right )-\lambda \right )+a \lambda \]

[_Riccati]

373.000

12303

\[ {}y^{\prime } = y^{2}-f \left (x \right )^{2}+f^{\prime }\left (x \right ) \]

[_Riccati]

1.112

12304

\[ {}y^{\prime } = y^{2} f \left (x \right )-f \left (x \right ) g \left (x \right ) y+g^{\prime }\left (x \right ) \]

[_Riccati]

1.586

12305

\[ {}y^{\prime } = -f^{\prime }\left (x \right ) y^{2}+f \left (x \right ) g \left (x \right ) y-g \left (x \right ) \]

[_Riccati]

1.684

12306

\[ {}y^{\prime } = g \left (x \right ) \left (y-f \left (x \right )\right )^{2}+f^{\prime }\left (x \right ) \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)]‘], _Riccati]

1.757

12307

\[ {}y^{\prime } = \frac {f^{\prime }\left (x \right ) y^{2}}{g \left (x \right )}-\frac {g^{\prime }\left (x \right )}{f \left (x \right )} \]

[_Riccati]

2.853

12308

\[ {}f \left (x \right )^{2} y^{\prime }-f^{\prime }\left (x \right ) y^{2}+g \left (x \right ) \left (y-f \left (x \right )\right ) = 0 \]

[_Riccati]

3.215

12309

\[ {}y^{\prime } = f^{\prime }\left (x \right ) y^{2}+a \,{\mathrm e}^{\lambda x} f \left (x \right ) y+a \,{\mathrm e}^{\lambda x} \]

[_Riccati]

2.245

12310

\[ {}y^{\prime } = y^{2} f \left (x \right )+g^{\prime }\left (x \right ) y+a f \left (x \right ) {\mathrm e}^{2 g \left (x \right )} \]

[_Riccati]

2.101

12311

\[ {}y^{\prime } = y^{2}-\frac {f^{\prime \prime }\left (x \right )}{f \left (x \right )} \]

[_Riccati]

1.154

12312

\[ {}y^{\prime } = y^{2}+a^{2} f \left (a x +b \right ) \]

[_Riccati]

1.276

12313

\[ {}y^{\prime } = y^{2}+\frac {f \left (\frac {1}{x}\right )}{x^{4}} \]

[_Riccati]

1.508

12314

\[ {}y^{\prime } = y^{2}+\frac {f \left (\frac {a x +b}{c x +d}\right )}{\left (c x +d \right )^{4}} \]

[_Riccati]

3.763

12315

\[ {}x^{2} y^{\prime } = x^{4} f \left (x \right ) y^{2}+1 \]

[_Riccati]

2.529

12316

\[ {}x^{2} y^{\prime } = y^{2} x^{4}+x^{2 n} f \left (a \,x^{n}+b \right )-\frac {n^{2}}{4}+\frac {1}{4} \]

[_Riccati]

5.615

12317

\[ {}y^{\prime } = y^{2} f \left (x \right )+g \left (x \right ) y+h \left (x \right ) \]

[_Riccati]

2.373

12318

\[ {}y^{\prime } = y^{2}+{\mathrm e}^{2 \lambda x} f \left ({\mathrm e}^{\lambda x}\right )-\frac {\lambda ^{2}}{4} \]

[_Riccati]

3.007

12319

\[ {}y^{\prime } = y^{2}-\frac {\lambda ^{2}}{4}+\frac {{\mathrm e}^{2 \lambda x} f \left (\frac {a \,{\mathrm e}^{\lambda x}+b}{c \,{\mathrm e}^{\lambda x}+d}\right )}{\left (c \,{\mathrm e}^{\lambda x}+d \right )^{4}} \]

[_Riccati]

45.047

12320

\[ {}y^{\prime } = y^{2}-\lambda ^{2}+\frac {f \left (\coth \left (\lambda x \right )\right )}{\sinh \left (\lambda x \right )^{4}} \]

[_Riccati]

37.645

12321

\[ {}y^{\prime } = y^{2}-\lambda ^{2}+\frac {f \left (\tanh \left (\lambda x \right )\right )}{\cosh \left (\lambda x \right )^{4}} \]

[_Riccati]

19.056

12322

\[ {}x^{2} y^{\prime } = x^{2} y^{2}+f \left (a \ln \left (x \right )+b \right )+\frac {1}{4} \]

[_Riccati]

2.317

12323

\[ {}y^{\prime } = y^{2}+\lambda ^{2}+\frac {f \left (\cot \left (\lambda x \right )\right )}{\sin \left (\lambda x \right )^{4}} \]

[_Riccati]

105.461

12324

\[ {}y^{\prime } = y^{2}+\lambda ^{2}+\frac {f \left (\tan \left (\lambda x \right )\right )}{\cos \left (\lambda x \right )^{4}} \]

[_Riccati]

25.556

12325

\[ {}y^{\prime } = y^{2}+\lambda ^{2}+\frac {f \left (\frac {\sin \left (\lambda x +a \right )}{\sin \left (\lambda x +b \right )}\right )}{\sin \left (\lambda x +b \right )^{4}} \]

[_Riccati]

453.227

12326

\[ {}y y^{\prime }-y = A \]

[_quadrature]

1.140

12327

\[ {}y y^{\prime }-y = A x +B \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

8.389

12328

\[ {}y y^{\prime }-y = -\frac {2 x}{9}+A +\frac {B}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

8.074

12329

\[ {}y y^{\prime }-y = 2 A \left (\sqrt {x}+4 A +\frac {3 A^{2}}{\sqrt {x}}\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.831

12330

\[ {}y y^{\prime }-y = A x +\frac {B}{x}-\frac {B^{2}}{x^{3}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.395

12331

\[ {}y y^{\prime }-y = A \,x^{k -1}-k B \,x^{k}+k \,B^{2} x^{2 k -1} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.321

12332

\[ {}y y^{\prime }-y = \frac {A}{x}-\frac {A^{2}}{x^{3}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.149

12333

\[ {}y y^{\prime }-y = A +B \,{\mathrm e}^{-\frac {2 x}{A}} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.374

12334

\[ {}y y^{\prime }-y = A \left ({\mathrm e}^{\frac {2 x}{A}}-1\right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

1.309

12335

\[ {}y y^{\prime }-y = -\frac {2 \left (m +1\right )}{\left (m +3\right )^{2}}+A \,x^{m} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.960

12336

\[ {}y y^{\prime }-y = -\frac {2 x}{9}+6 A^{2} \left (1+\frac {2 A}{\sqrt {x}}\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.420

12337

\[ {}y y^{\prime }-y = \frac {2 m -2}{\left (m -3\right )^{2}}+\frac {2 A \left (m \left (m +3\right ) \sqrt {x}+\left (4 m^{2}+3 m +9\right ) A +\frac {3 m \left (m +3\right ) A^{2}}{\sqrt {x}}\right )}{\left (m -3\right )^{2}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

39.916

12338

\[ {}y y^{\prime }-y = \frac {\left (2 m +1\right ) x}{4 m^{2}}+\frac {A}{x}-\frac {A^{2}}{x^{3}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.874

12339

\[ {}y y^{\prime }-y = \frac {4}{9} x +2 A \,x^{2}+2 A^{2} x^{3} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.354

12340

\[ {}y y^{\prime }-y = -\frac {3 x}{16}+\frac {5 A}{x^{{1}/{3}}}-\frac {12 A^{2}}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.155

12341

\[ {}y y^{\prime }-y = \frac {A}{x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.651

12342

\[ {}y y^{\prime }-y = -\frac {x}{4}+\frac {A \left (\sqrt {x}+5 A +\frac {3 A^{2}}{\sqrt {x}}\right )}{4} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.792

12343

\[ {}y y^{\prime }-y = \frac {2 a^{2}}{\sqrt {8 a^{2}+x^{2}}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

2.319

12344

\[ {}y y^{\prime }-y = 2 x +\frac {A}{x^{2}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.972

12345

\[ {}y y^{\prime }-y = -\frac {6 X}{25}+\frac {2 A \left (2 \sqrt {x}+19 A +\frac {6 A^{2}}{\sqrt {x}}\right )}{25} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

27.727

12346

\[ {}y y^{\prime }-y = \frac {3 x}{8}+\frac {3 \sqrt {a^{2}+x^{2}}}{8}-\frac {a^{2}}{16 \sqrt {a^{2}+x^{2}}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

5.269

12347

\[ {}y y^{\prime }-y = -\frac {4 x}{25}+\frac {A}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.934

12348

\[ {}y y^{\prime }-y = -\frac {9 x}{100}+\frac {A}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

40.636

12349

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+\frac {2 A \left (5 \sqrt {x}+34 A +\frac {15 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.279

12350

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+\frac {A \left (25 \sqrt {x}+41 A +\frac {10 A^{2}}{\sqrt {x}}\right )}{98} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.194

12351

\[ {}y y^{\prime }-y = -\frac {2 x}{9}+\frac {A}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.704

12352

\[ {}y y^{\prime }-y = -\frac {5 x}{36}+\frac {A}{x^{{7}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

47.919

12353

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+\frac {6 A \left (-3 \sqrt {x}+23 A +\frac {12 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.126

12354

\[ {}y y^{\prime }-y = -\frac {30 x}{121}+\frac {3 A \left (21 \sqrt {x}+35 A +\frac {6 A^{2}}{\sqrt {x}}\right )}{242} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.221

12355

\[ {}y y^{\prime }-y = -\frac {3 x}{16}+\frac {A}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

39.997

12356

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+\frac {4 A \left (-10 \sqrt {x}+27 A +\frac {10 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.500

12357

\[ {}y y^{\prime }-y = \frac {A}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.724

12358

\[ {}y y^{\prime }-y = \frac {A}{x^{2}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.732

12359

\[ {}y y^{\prime }-y = A \left (n +2\right ) \left (\sqrt {x}+2 \left (n +2\right ) A +\frac {\left (n +1\right ) \left (n +3\right ) A^{2}}{\sqrt {x}}\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

17.169

12360

\[ {}y y^{\prime }-y = A \left (n +2\right ) \left (\sqrt {x}+2 \left (n +2\right ) A +\frac {\left (2 n +3\right ) A^{2}}{\sqrt {x}}\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

19.791

12361

\[ {}y y^{\prime }-y = A \sqrt {x}+2 A^{2}+\frac {B}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

11.220

12362

\[ {}y y^{\prime }-y = 2 A^{2}-A \sqrt {x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.016

12363

\[ {}y y^{\prime }-y = -\frac {x}{4}+\frac {6 A \left (\sqrt {x}+8 A +\frac {5 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.161

12364

\[ {}y y^{\prime }-y = -\frac {6 x}{25}+\frac {6 A \left (2 \sqrt {x}+7 A +\frac {4 A^{2}}{\sqrt {x}}\right )}{25} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.636

12365

\[ {}y y^{\prime }-y = -\frac {3 x}{16}+\frac {3 A}{x^{{1}/{3}}}-\frac {12 A^{2}}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.965

12366

\[ {}y y^{\prime }-y = \frac {3 x}{8}+\frac {3 \sqrt {b^{2}+x^{2}}}{8}+\frac {3 b^{2}}{16 \sqrt {b^{2}+x^{2}}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

5.057

12367

\[ {}y y^{\prime }-y = \frac {9 x}{32}+\frac {15 \sqrt {b^{2}+x^{2}}}{32}+\frac {3 b^{2}}{64 \sqrt {b^{2}+x^{2}}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

6.453

12368

\[ {}y y^{\prime }-y = -\frac {3 x}{32}-\frac {3 \sqrt {a^{2}+x^{2}}}{32}+\frac {15 a^{2}}{64 \sqrt {a^{2}+x^{2}}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

5.589

12369

\[ {}y y^{\prime }-y = A \,x^{2}-\frac {9}{625 A} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

0.931

12370

\[ {}y y^{\prime }-y = -\frac {6}{25} x -A \,x^{2} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

0.901

12371

\[ {}y y^{\prime }-y = \frac {6}{25} x -A \,x^{2} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

0.905

12372

\[ {}y y^{\prime }-y = 12 x +\frac {A}{x^{{5}/{2}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.219

12373

\[ {}y y^{\prime }-y = \frac {63 x}{4}+\frac {A}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

45.341

12374

\[ {}y y^{\prime }-y = 2 x +2 A \left (10 \sqrt {x}+31 A +\frac {30 A^{2}}{\sqrt {x}}\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.043

12375

\[ {}y y^{\prime }-y = 2 x +2 A \left (-10 \sqrt {x}+19 A +\frac {30 A^{2}}{\sqrt {x}}\right ) \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.215

12376

\[ {}y y^{\prime }-y = -\frac {28 x}{121}+\frac {2 A \left (5 \sqrt {x}+106 A +\frac {65 A^{2}}{\sqrt {x}}\right )}{121} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.110

12377

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+\frac {A \left (5 \sqrt {x}+262 A +\frac {65 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.160

12378

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+A \sqrt {x} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.964

12379

\[ {}y y^{\prime }-y = 6 x +\frac {A}{x^{4}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.898

12380

\[ {}y y^{\prime }-y = 20 x +\frac {A}{\sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.696

12381

\[ {}y y^{\prime }-y = \frac {15 x}{4}+\frac {A}{x^{7}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

0.957

12382

\[ {}y y^{\prime }-y = -\frac {10 x}{49}+\frac {2 A \left (4 \sqrt {x}+61 A +\frac {12 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.430

12383

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+\frac {2 A \left (\sqrt {x}+166 A +\frac {55 A^{2}}{\sqrt {x}}\right )}{49} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

7.105

12384

\[ {}y y^{\prime }-y = -\frac {4 x}{25}+\frac {A \left (7 \sqrt {x}+49 A +\frac {6 A^{2}}{\sqrt {x}}\right )}{50} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.914

12385

\[ {}y y^{\prime }-y = \frac {15 x}{4}+\frac {6 A}{x^{{1}/{3}}}-\frac {3 A^{2}}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

4.131

12386

\[ {}y y^{\prime }-y = -\frac {3 x}{16}+\frac {A}{x^{{1}/{3}}}+\frac {B}{x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

15.298

12387

\[ {}y y^{\prime }-y = -\frac {5 x}{36}+\frac {A}{x^{{3}/{5}}}-\frac {B}{x^{{7}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

9.079

12388

\[ {}y y^{\prime }-y = \frac {k}{\sqrt {A \,x^{2}+B x +c}} \]

[[_Abel, ‘2nd type‘, ‘class B‘]]

3.876

12389

\[ {}y y^{\prime }-y = -\frac {12 x}{49}+3 A \left (\frac {1}{49}+B \right ) \sqrt {x}+3 A^{2} \left (\frac {4}{49}-\frac {5 B}{2}\right )+\frac {15 A^{3} \left (\frac {1}{49}-\frac {5 B}{4}\right )}{4 \sqrt {x}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.106

12390

\[ {}y y^{\prime }-y = -\frac {6 x}{25}+\frac {4 B^{2} \left (\left (2-A \right ) x^{{1}/{3}}-\frac {3 B \left (2 A +1\right )}{2}+\frac {B^{2} \left (1-3 A \right )}{x^{{1}/{3}}}-\frac {A \,B^{3}}{x^{{2}/{3}}}\right )}{75} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.966

12391

\[ {}y y^{\prime }-y = \frac {3 x}{4}-\frac {3 A \,x^{{1}/{3}}}{2}+\frac {3 A^{2}}{4 x^{{1}/{3}}}-\frac {27 A^{4}}{625 x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

8.249

12392

\[ {}y y^{\prime }-y = -\frac {6 x}{25}+\frac {7 A \,x^{{1}/{3}}}{5}+\frac {31 A^{2}}{3 x^{{1}/{3}}}-\frac {100 A^{4}}{3 x^{{5}/{3}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

8.040

12393

\[ {}y y^{\prime }-y = -\frac {10 x}{49}+\frac {13 A^{2}}{5 x^{{1}/{5}}}-\frac {7 A^{3}}{20 x^{{4}/{5}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

14.849

12394

\[ {}y y^{\prime }-y = -\frac {33 x}{169}+\frac {286 A^{2}}{3 x^{{5}/{11}}}-\frac {770 A^{3}}{9 x^{{13}/{11}}} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

37.519

12395

\[ {}y y^{\prime }-y = -\frac {21 x}{100}+\frac {7 A^{2} \left (\frac {123}{x^{{1}/{7}}}+\frac {280 A}{x^{{5}/{7}}}-\frac {400 A^{2}}{x^{{9}/{7}}}\right )}{9} \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

32.616

12396

\[ {}y y^{\prime }-y = a x +b \,x^{m} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.605

12397

\[ {}y y^{\prime }-y = -\frac {\left (m +1\right ) x}{\left (m +2\right )^{2}}+A \,x^{2 m +1}+B \,x^{3 m +1} \]

[_rational, [_Abel, ‘2nd type‘, ‘class A‘]]

12.206

12398

\[ {}y y^{\prime }-y = a^{2} \lambda \,{\mathrm e}^{2 \lambda x}-a \left (b \lambda +1\right ) {\mathrm e}^{\lambda x}+b \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.701

12399

\[ {}y y^{\prime }-y = a^{2} \lambda \,{\mathrm e}^{2 \lambda x}+a \lambda x \,{\mathrm e}^{\lambda x}+b \,{\mathrm e}^{\lambda x} \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

2.227

12400

\[ {}y y^{\prime }-y = 2 a^{2} \lambda \sin \left (2 \lambda x \right )+2 a \sin \left (\lambda x \right ) \]

[[_Abel, ‘2nd type‘, ‘class A‘]]

7.118